Interplay Between MW, ΩCDMh2, and g−2μ in Flavor Symmetry–Based Supersymmetric Models - Sajid Israr; Mario E. Gómez; Muhammad Rehman; Yasir Arafat (Advances in High Energy Physics, 2025)
We study the phenomenological implications of the minimal supersymmetric standard model (MSSM) augmented by a nonabelian flavor symmetry labeled as sMSSM. Incorporating this flavor symmetry allows for a significant reduction in the original plethora of free parameters present in the MSSM, ultimately reducing them down to just seven in sMSSM. This reduction of free parameters is not achieved through ad hoc assumptions like in the constrained MSSM (CMSSM); rather, it is grounded in theoretical considerations. Our work focuses on exploring the interplay between the W boson mass (MW) predictions, the cold dark matter (CDM) relic abundance ΩCDMh2, and the g−2μ anomaly. We identified correlations among the theoretical parameters arising from this interplay, which can be complemented by experimental constraints such as the Higgs boson mass, B-physics observables, and charge and color breaking minima. Additionally, our investigations show that the g−2μ discrepancy and the Planck bounds on ΩCDMh2 can be addressed within the sMSSM but only in a very narrow region of the parameter space.